2011
DOI: 10.1371/journal.pone.0023577
|View full text |Cite
|
Sign up to set email alerts
|

Serum-Nutrient Starvation Induces Cell Death Mediated by Bax and Puma That Is Counteracted by p21 and Unmasked by Bcl-xL Inhibition

Abstract: The cyclin-dependent kinase inhibitor p21 (p21WAF1/Cip1) is a multifunctional protein known to promote cell cycle arrest and survival in response to p53-dependent and p53 independent stimuli. We herein investigated whether and how it might contribute to the survival of cancer cells that are in low-nutrient conditions during tumour growth, by culturing isogenic human colorectal cancer cell lines (HCT116) and breast cancer cell lines in a medium deprived in amino acids and serum. We show that such starvation enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 34 publications
6
59
1
3
Order By: Relevance
“…These results suggest that p53 is induced and is required for neuron death in response to A␤. It is known that both A␤ and p53 induce BAX (2, 44, 45), which acts as a downstream effector of PUMA in the cell death cascade (46,47). Therefore, we checked the level of Bax and found that it was elevated in response to A␤ (Fig.…”
Section: Puma Is Induced In Neurons In Response To A␤ In Cultures and Inmentioning
confidence: 93%
“…These results suggest that p53 is induced and is required for neuron death in response to A␤. It is known that both A␤ and p53 induce BAX (2, 44, 45), which acts as a downstream effector of PUMA in the cell death cascade (46,47). Therefore, we checked the level of Bax and found that it was elevated in response to A␤ (Fig.…”
Section: Puma Is Induced In Neurons In Response To A␤ In Cultures and Inmentioning
confidence: 93%
“…Previous evidence has shown that nutrition deprivation causes cancer cell death (30). Braun et al demonstrated that serum-nutrient starvation induces cell death mediated by Bax and Puma (31). However, under the condition of nutrient/oxygen depletion, cancer cells are expected to be more sensitive towards an apoptotic inducer.…”
Section: Discussionmentioning
confidence: 99%
“…Braun et al [40] observed that starvation induces the increase of p21 levels in MCF7 cell lines independently from p53 and this mitigates the efficacy of the Puma/Baxdependent apoptotic signal (also induced by starvation). In addition, the anti-apoptotic function exerted by p21 in starved cells occurs upstream of mitochondrial permeabilization at the level of the Puma interactions with Bcl-x.…”
Section: Dietary Restriction-induced Molecular Changesmentioning
confidence: 99%